Downward Revision of Investment Decisions after Corporate Tax Hikes - Sebastian Link; Manuel Menkhoff; Andreas Peichl; Paul Schüle (Institute of Labor Economics (IZA), 2023)
This paper estimates the causal effect of corporate tax hikes on firm investment based on more than 1,400 local tax changes. By observing planned and realized investment volumes in a representative sample of German manufacturing firms, we can study how tax hikes induce firms to revise their investment decisions. On average, the share of firms that invest less than previously planned increases by three percentage points after a tax hike. This effect is twice as large during recessions.
Keywords: G11; H25; H32; H71; O16; 330; investment; corporate taxation; state dependence; business cycle